Volume 2B: Turbomachinery 2018
DOI: 10.1115/gt2018-76994
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study of Using Vortex Generators As Tip Leakage Flow Interrupters in an Axial Flow Turbine Stage

Abstract: The flow leaking through the gap between rotor blade tips and casing surface in a turbine stage is an important source of energy loss. The current study uses a new concept named as Tip Leakage Interrupters (TLI) to mitigate some of the adverse effects of the tip leakage flows and improve the efficiency of an axial turbine stage. The TLIs are a system of vortex generators attached onto the suction side of the turbine blade tip. The TLI design was developed in a proof of concept effort and they operate by induci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Results showed that it is difficult for the ACL to have a satisfactory inhibitory effect on TLV cavitation, and once the vortex generators are not operating under design conditions, a more intense level of cavitation will be induced. 137,176 A recent numerical study by Kadivar et al 177 proposed a new type of VG called cavitating bubble generators (CGs) (Fig. 19).…”
Section: Physics Of Fluidsmentioning
confidence: 99%
“…Results showed that it is difficult for the ACL to have a satisfactory inhibitory effect on TLV cavitation, and once the vortex generators are not operating under design conditions, a more intense level of cavitation will be induced. 137,176 A recent numerical study by Kadivar et al 177 proposed a new type of VG called cavitating bubble generators (CGs) (Fig. 19).…”
Section: Physics Of Fluidsmentioning
confidence: 99%
“…13 Tip clearance and the number of blades in a propeller are additional design considerations that impact performance. [14][15][16][17][18][19][20][21][22][23][24] The use of ducts is then limited in certain circumstances, researchers aim in this case to improve the performance of the propeller system otherwise. Optimizing propeller shape, including chord length, pitch angle, twist, sweep, and lean, is crucial for efficient and highperformance propellers.…”
Section: Introductionmentioning
confidence: 99%
“…and suction side (S.S.), overtip leakage (OTL) generates in the tip gap, resulting in pronounced aerodynamic loss and increased thermal load in the tip region of high pressure (HP) gas turbine stage. 1 To reduce the thermal load and improve the aerodynamic performance in blade tip region, many innovative tip designs and advanced cooling schemes have been presented in the modern gas turbine community 2 In HP turbine stages, the squealer tips are commonly applied due to their superior aerodynamic performance and relatively low thermal load as compared with the flat tips. 1 Evidences have shown that the P.S.…”
Section: Introductionmentioning
confidence: 99%
“…and suction side (S.S.), overtip leakage (OTL) generates in the tip gap, resulting in pronounced aerodynamic loss and increased thermal load in the tip region of high pressure (HP) gas turbine stage. 1 To reduce the thermal load and improve the aerodynamic performance in blade tip region, many innovative tip designs and advanced cooling schemes have been presented in the modern gas turbine community 2…”
Section: Introductionmentioning
confidence: 99%